2008
DOI: 10.1016/j.corsci.2008.08.049
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of coating performance by the variations of phase angles in middle and high frequency domains of EIS

Abstract: Electrical impedance spectroscopy (EIS), in which a sinusoidal test voltage or current is applied to the sample under test to measure its impedance over a suitable frequency range, is a powerful technique to investigate the electrical properties of a large variety of materials. In practice, the measured impedance spectra, usually fitted with an equivalent electrical model, represent an electrical fingerprint of the sample providing an insight into its properties and behavior. EIS is used in a broad range of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(66 citation statements)
references
References 52 publications
5
61
0
Order By: Relevance
“…For intact coatings, the coating resistance R po is much higher compared with the electrochemical reaction parameters [57]. Supposing the solution resistance R s is negligible, during the early period of immersion the equivalent circuit may be approximately expressed as a parallel connection of R po and C c , the impedance of which has following form [58,59]:…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…For intact coatings, the coating resistance R po is much higher compared with the electrochemical reaction parameters [57]. Supposing the solution resistance R s is negligible, during the early period of immersion the equivalent circuit may be approximately expressed as a parallel connection of R po and C c , the impedance of which has following form [58,59]:…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…For this reason, many authors have investigated the possibility to use only raw impedance data. Mahdavian and Attar (2006) found that the phase angle at 10 kHz can be used to estimate coating resistance and capacitance; Zuo et al (2008) extended the investigations of Mahadavian and Attar and discussed how the phase angle measured at 10 Hz is correlated with the coating resistance, while the value measured at 15 kHz can be used to detect the loss of coating protection; Akbarinezhad et al (2009) suggested that the area under the Bode plot for |Z| and Arg(Z) provides a parameter for ranking the performance of organic coating; Zhang et al (2005) discussed how the breakpoint frequency (i.e., that at which the phase angle equals 45 • ) is proportional to the delaminated area and inversely proportional to coating resistivity and permittivity; Zhao et al (2007) used the changing rate of impedance in conjunction with the self-organizing feature map network for the analysis of the coating deterioration process. An handheld system for in situ corrosion monitoring, based on the microcontroller MSP430F149 and capable of measuring impedances in the range 1 k -10 G was built by Angelini et al (2006).…”
Section: Other Eis Applicationsmentioning
confidence: 99%
“…This phenomenon leads to an increase in the Rct values at longer than the 622 h of immersion. Moreover, considering Figure 7b, the phase depression and shift during the immersion times confirms the water adsorption phenomenon through the coating micro porosities [23,25,26,28]. According to the measured impedance values of the coating, it can be deduced that the coating resistance is increased during the whole immersion times which could be due to obstruction of the micro porosities by possible reaction products such as salts [23,24,26].…”
Section: Electrochemical Measurementsmentioning
confidence: 84%
“…This study investigates the electrochemical and microbiological properties of beeswax-colophony green mixture as a proposed coating for drinking water storage tanks. In order to assess the coating performance in preventing corrosion or fouling, electrochemical techniques such as electrochemical impedance spectroscopy (EIS) have been previously used in chloride containing solutions [23][24][25][26][27][28][29][30][31][32][33][34]. Therefore, in this study, the long-term electrochemical behavior of the coating was studied in 3.5 wt.…”
Section: Introductionmentioning
confidence: 99%